2011
DOI: 10.1186/1471-2202-12-117
|View full text |Cite
|
Sign up to set email alerts
|

Functional coupling analysis suggests link between the obesity gene FTO and the BDNF-NTRK2 signaling pathway

Abstract: BackgroundThe Fat mass and obesity gene (FTO) has been identified through genome wide association studies as an important genetic factor contributing to a higher body mass index (BMI). However, the molecular context in which this effect is mediated has yet to be determined. We investigated the potential molecular network for FTO by analyzing co-expression and protein-protein interaction databases, Coxpresdb and IntAct, as well as the functional coupling predicting multi-source database, FunCoup. Hypothalamic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The few studies that have been performed place FTO amid complex gene interactions involved in both lipolysis and eating behavior. For example, there is support that FTO participates in regulating neuronal plasticity through interactions with brain-derived neurotropic factor (BDNF) and type 2 neurotropic tyrosine kinase receptor [15]. Along with its role in neuronal development and survival, variants in the BDNF gene have been significantly associated with weight gain, and a number of studies have targeted BDNF for a role in energy expenditure and AIWG [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have been performed place FTO amid complex gene interactions involved in both lipolysis and eating behavior. For example, there is support that FTO participates in regulating neuronal plasticity through interactions with brain-derived neurotropic factor (BDNF) and type 2 neurotropic tyrosine kinase receptor [15]. Along with its role in neuronal development and survival, variants in the BDNF gene have been significantly associated with weight gain, and a number of studies have targeted BDNF for a role in energy expenditure and AIWG [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, homozygous AA individuals are more prone to an elevated post‐prandial appetite level, which is linked to an interaction between the FTO genotype and circulating levels of ghrelin, a key mediator of digestive behavior (Karra et al, ). Other studies also suggest an effect of FTO on the regulation of proteins in pathways involved in energy intake, such as leptin levels (Labayen et al, ) and leptin sensitivity (Wang et al, ), and other signaling proteins (Lin et al, ; Rask‐Andersen et al, ). The FTO ‐rs9939609 genotype is also associated with some metabolites, with evidence having been obtained of changes in phospholipid and amino acid metabolisms that may be linked to obesity and type 2 diabetes in A allele carriers (Kim et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…However, the existing papers showed that feeding status had indeed affected FTO mRNA expression. Hypothalamic FTO mRNA levels have been reported to be higher (Fredriksson et al, 2008;Olszewski et al, 2009;Rask-Andersen et al, 2011), decreased (Poritsanos et al, 2011 or without difference (McTaggart et al, 2011) in fasted mice. Fasting was also found to change hepatic FTO mRNA expression, but had no effect on FTO mRNA expression in muscle and adipose tissues both in mice and broiler chickens (Poritsanos et al, 2010;McTaggart et al, 2011;Tiwari et al, 2012).…”
Section: Discussionmentioning
confidence: 99%